Penanganan Pasien Perdarahan Intraserebral di Ruang Rawat Intensif - Ibrahim, Rian; Lalenoh, Diana Ch.; Laihad, Mordekhai L. (e-CliniC, 2021)
Abstract: Intracerebral haemorrhage is a type of intracranial haemorrhage that occurs due to rupture of blood vessels in the brain tissue which is caused by trauma, hypertension, and nonhypertension. The intensive care unit is a separate section within the hospital that treats patients with life-threatening conditions, undergoing resuscitation, requiring intensive care and monitoring, and containing equipment and medicines to maintain normal body functions. All patients who are treated with intracerebral haemorrhage in intensive care unit should receive attention in terms of radiological evaluation, maintaining adequate respiration and circulation, controlling intracranial pressure, controlling blood pressure, preventing hyperglycemia, hypotension, and fever, controlling neurosurgical surgeries as well as preventing seizures. Surgery is performed to evacuate the accessible hematoma, depending on the location of the hematoma in intracerebral. In general, management of the patients aims to minimize nerve damage, prevent and treat systemic complications, speed recovery, and prevent or slow down recurrences and complications. Outcome of patient with intracerebral haemorrhage will be better if the patient is treated specifically in the intensive care unit.Keywords: management, intracerebral haemorrhage, intensive care unitÂ Abstrak: Perdarahan intraserebral terjadi akibat robeknya pembuluh darah dalam jaringan otak yang dapat disebabkan oleh trauma, hipertensi, dan non hipertensi. Ruang rawat intensif merupakan bagian tersendiri di dalam rumah sakit yang merawat pasien dengan kondisi mengancam jiwa, yang sedang menjalani resusitasi, membutuhkan perawatan dan pemantauan secara intensif, serta yang didalamnya terdapat peralatan maupun obat-obatan yang berguna untuk menjaga fungsi tubuh seperti normal. Semua penderita yang dirawat dengan perdarahan intraserebral di ruang rawat intensif harus mendapat perhatian dalam hal evaluasi radiologik, menjaga adekuatnya respirasi dan sirkulasi, pengendalian tekanan intrakranial, pengendalian tekanan darah, pencegahan hiperglikemi, hipotensi dan demam, pengontrolan terhadap operasi pembedahan saraf dan pencegahan kejang. Pembedahan dilakukan untuk evakuasi hematom yang dapat dijangkau, tergantung lokasi hematoma di intraserebral. Penanganan yang dilakukan bertujuan untuk meminimalkan kerusakan saraf, mencegah dan mengobati komplikasi sistemik yang terjadi, mempercepat pemulihan dan mencegah atau memperlambat kekambuhan dan komplikasi. Outcome pasien perdarahan intraserebral akan lebih baik, jika pasien dirawat khusus di ruang rawat intensif.Kata kunci: penanganan, perdarahan intrasereberal, ruang rawat intensif